Exploring the impact of sleep on emotional and physical well-being in professional cricketers: a cohort study over an in-season training period - Grewal, S.; Theijse, R. T.; Dunlop, G.; van Deurzen, D. F. P.; van den Bekerom, M. P. J.; Klautz, R. J. M.; Lefebvre, R. P.; Munsami, D.; Grewal, N. (Frontiers in Sports and Active Living, 2024)
Background: Sleep plays a key role in proper biopsychosocial development as well as shortand long-term biological, physical, psychological, and cognitive health. As poor sleep quality is known to impair proper brain function, this study aimed to investigate the effect of sleep quality on a professional athlete's ability to train, recover, and perform, and their overall emotional and physical well-being. Methods: A cohort study was performed in 40 professional male cricket athletes from the Dutch national cricket team (mean age 26.5 ± 5.1 years). Sleep quality and overall emotional and physical well-being were assessed using daily sleep diaries and questionnaires which scored the readiness to train, stress levels, fatigue, muscle soreness and flu symptoms respectively. Data were accumulated over a 22-weeks in-season training period. Results: The athletes assessed their sleep quality as average with a mean score of 3.4 out of 5. Lower perceived quality of sleep (<75 th percentile) was correlated with an increased extent of muscle soreness (2.7 vs. 2.3), decreased readiness to train (mean score 3.2 vs. 3.5), increased stress level (mean score 2.3 vs. 1.9) and increased perceived fatigue (mean score 2.9 vs. 2.3). Likewise, in patients with lower perceived quality of sleep, the proportion of players presenting with flu symptoms increased over 4-fold (4.1% vs. 17%; P<0.001). Conclusions: This study highlights that good sleep quality positively influences the overall emotional and physical well-being of professional athletes. Our results emphasize the importance of targeted sleep interventions to improve sleep quality and subsequently optimize psychological and physiological wellness.